2018
DOI: 10.12659/msm.909627
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin, a Chinese Herbal Medicine, Inhibits the Proliferation and Migration of Human Non-Small Cell Lung Carcinoma (NSCLC) Cells, A549 and H1299, by Activating the SIRT1/AMPK Signaling Pathway

Abstract: BackgroundBaicalin is a flavonoid derived from Scutellaria baicalensis, used in Chinese herbal medicine. Activation of the sirtuin 1 gene (SIRT1) and adenosine monophosphate (AMP)-activated protein kinase gene (AMPK), the SIRT1/AMPK signaling pathway, is associated with human malignant tumors. The aim of this study was to investigate the effects of baicalin on the cell viability, apoptosis, proliferation, and migration of human non-small cell lung cancer (NSCLC) cells, A549 and H1299, in vitro.Material/Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 27 publications
(25 reference statements)
3
46
0
Order By: Relevance
“…AMPK not only senses the changes in cellular energy levels, but also responds to reactive oxygen species and activates processes such as apoptosis and autophagy [38]. A recent study demonstrated AMPK-mediated inhibition of cancer cell proliferation by BC [39]. As shown in Figure 3, we observed an altered AMPK phosphorylation in the BPH group as compared to the control group.…”
Section: Discussionsupporting
confidence: 53%
“…AMPK not only senses the changes in cellular energy levels, but also responds to reactive oxygen species and activates processes such as apoptosis and autophagy [38]. A recent study demonstrated AMPK-mediated inhibition of cancer cell proliferation by BC [39]. As shown in Figure 3, we observed an altered AMPK phosphorylation in the BPH group as compared to the control group.…”
Section: Discussionsupporting
confidence: 53%
“…A natural polyphenolic compound, resveratrol, has been shown to promote the expression of SIRT1 in rat ovarian granulosa cells, which implicated the important role of SIRT1 in ovarian function [33]. It has been shown that BAL inhibits the proliferation and migration of human non-small cell lung carcinoma cells through activation of the SIRT1/AMPK signaling pathway [15]. In contrast, Xu et al showed that BAL inhibited SIRT1-induced regulation of signal transducer and activator of transcription 3 (STAT3), leading to the suppression of excessive hepatic glucose production [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we aimed to evaluate the effects of BAL on the dysregulation of hormones, histological changes of the ovary, and metabolic disorder in PCOS rats. Previous literature and our preliminary studies have suggested that activation of AMP-activated protein kinase (AMPK) is associated with the beneficial effects of BAL [15]. Thus, we examined the potential involvement of AMPK in BAL-induced effects on PCOS rats.…”
Section: Introductionmentioning
confidence: 94%
“…The abnormal increase in estrogens and their metabolites can easily lead to cholestasis, which results in the impairment of bile flow and hepatotoxicity (Trauner et al, 1998). Baicalin is the main flavonoid component isolated from the traditional Chinese medicine Scutellaria baicalensis (You et al, 2018). In previous studies, it has been revealed that baicalin possess effective therapeutic effects on liver diseases (Guo et al, 2009;Dai et al, 2018;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%